FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS KUTA BLANG KABUPATEN BIREUEN - Armiatin, Armiatin (Jurnal Cakrawala Ilmiah, 2024)
Background: Stunting is a major nutritional problem that occurs in developing countries. (UNICEF) stated that around 80% of stunted children are found in 24 developing countries in Asia and Africa. Indonesia is the fifth country with the highest prevalence of stunted children after India, China, Nigeria and Pakistan. Research Objective: To determine the factors related to the incidence of stunting in the UPTD Work Area of ​​Kuta Blang Health Center, Bireuen Regency in 2024. Research design: Quantitative (survey analysis) with a cross sectional study approach. The population of all mothers who have toddlers who are at risk of stunting in the Kuta Blang Community Health Center Working Area, Bireuen Regency is 63 mothers of toddlers. The sampling technique used in this research was the total population of all populations used as the sample. Research Results: There is a relationship between knowledge and the incidence of stunting where the p-value = 0.000 (p-value ≤ 0.05). There is a relationship between family income and the incidence of stunting where the p-value = 0.000 (p-value ≤ 0.05). There is a relationship between exclusive breastfeeding and the incidence of stunting where the p-value = 0.015 (p-value ≤ 0.05). Suggestion: It is hoped that the health department, as the person responsible for specific and sensitive interventions, can develop efforts to accelerate stunting reduction.